TASK BASED LANGUAGE TEACHING TO IMPROVE STUDENTS’ WILLINGNESS TO COMMUNICATE IN ENGLISH CLASS - Nopita Trihastutie; Eka Fadilah (Berumpun: International Journal of Social, Politics, and Humanities, 2019)
The changing of English language teaching method from Audio-lingual Method to Communicative Language Teaching (CLT) has given great impact to the pedagogy of teaching English as a Foreign Language (EFL) and/ or English as a Second Language (ESL). Task Based Language Teaching (TBLT) method which emphasizes more on the meaning of a language and targeted tasks, then, dominates the English teaching world as a response to the un-satisfaction towards the previous methods (Long, 2015). This current study aims at seeing to what extent the task variety influences students’ willingness to communicate based on three contexts which include trait-like, situation, and linguistic. Three communicative tasks which emphasizes both on focused meaning and focused form were given. The communicative tasks include game, problem solving, and jigsaw. Observation was done during class interaction and continued with in depth interview. The result shows that emotion, class situation, and cognitive simultaneously influence the students’ willingness to communicate in English class. Those factors are inseparable, interact and influence interchangeably on the students’ willingness to communicate in English class as elucidated in complex dynamic theory.